FAKTOR-FAKTOR YANG MEMPENGARUHI PILIHAN KONSUMEN TERHADAP KOPI TOMORO DIBANDINGKAN MEREK LAIN (STUDI PENELITIAN GROUNDED THEORY) - Abhiyoga Deyandra Putra; Muhammad Feyzel Khalfani Putra Ardaneswo; Samsul Arifin; Jerry Heykal (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The research aims to capture the voices of Indonesian coffee consumers and develop a nuanced understanding of their preference for Tomoro Coffee. This will contribute valuable knowledge to the existing body of research on consumer behavior in the Indonesian coffee market and provide actionable insights for Tomoro Coffee's future marketing strategies. The approach utilized in this research employs a qualitative method based on grounded theory principles, enabling researchers to develop constructs and theories directly from data collected firsthand, rather than relying on pre-existing theories. Furthermore, the classification of categories into broader themes was carried out to identify the relationships among the compiled categories. Based on the study results, three major themes emerged from interviews with three business actors: Product Characteristics, Brand Image and Marketing, and Price and Value Perception. It can be concluded from the study results that the factors influencing consumer choice of Tomoro Coffee over other brands include the price and the value of the service and products obtained from Tomoro Coffee. Brand image and marketing also influence consumer choice because attractive marketing and promotions draw consumers to purchase Tomoro Coffee. Meanwhile, the variety of the menu, although not dominant, still serves as a reference for consumers to purchase Tomoro Coffee, particularly due to the delicious coffee flavors and affordable prices for consumers. In summary, the research highlights that the key factors driving consumer preference for Tomoro Coffee are competitive pricing, perceived value, effective marketing, and the quality of the product offerings. These insights can help Tomoro Coffee refine its marketing strategies and product development to better meet the needs and preferences of Indonesian coffee consumers. Keywords: Indonesian Coffee Market; Tomoro Coffee; Marketing Strategies; Qualitative Research; Grounded Theory.